Modern groundwater exploration discovering new water resources in consolidated rocks using innovative hydrogeologic concepts, exploration, drilling, aquifer testing, and management methods /: discovering new water resources in consolidated rocks using innovative hydrogeologic concepts, exploration, drilling, aquifer testing, and management methods. (©2004) - Unknown
No abstract available